Seamen's Bethel, ca. 1865 - Hawes, Josiah Johnson (Tufts Archival Research Center, 2005)
Street-level view south-southeast of the Seamen's Bethel, located at the southwest corner of North Square and Sun-Court Street. The facade of the building faces north-northwest towards North Square. 12 North Square is visible to the west-southwest or to the right of the Seamen's Bethel. 1 North Square is visible along the left side of the photograph. Signage adorns the facade of both the Seamen's Bethel and 1 North Square. 7 in diameter (image is round) Albumen prints